P72 Knowledge and use of contraceptive methods in portuguese women with systemic lupus erythematosus. (23rd March 2020) - Brites, Luisa; Silva, Stefanie; Andreoli, Laura; Inês, Luis
Abstract : Background: Systemic lupus erythematosus (SLE) affects women of childbearing age. Therefore contraceptive/family counselling are crucial to avoid unintended pregnancies. Our aim was to identify unmet needs for contraceptive/family counselling in women with SLE. Methods: Cross-sectional study including women aged 18–45 year-old fulfilling ACR 1997/SLICC criteria. All patients signed an informed consent and fulfilled a questionnaire with 15 short answers questions evaluating 4 domains: brief obstetric history; knowledge about the relationship between pregnancy and SLE, contraceptive/family counselling, contraception use and type of medical care offered. A descriptive analysis was used to summarize demographic/clinical data; possible predictors of contraceptive use (age, previous spontaneous abortion, level of knowledge about SLE, contraceptive/family planning) were tested by multiple regression analysis using SPSS Statistics, V.21; p <0.05 was considered statistically significant. Results: We enrolled 108 women (mean age 34.4±7.1 years; mean disease duration 10.3±7.3 years). About 65% of the included patients received information about family planning (mostly from rheumatologists (62.9%)) and 81% received information about contraception (mostly from gynaecologists (56.3%)). Only 38% was considered informed about SLE and its influence in pregnancy. In this cohort, 23.1% wanted to get pregnant in the next 6 months; the rest of them already had the number of children they wanted or wanted to get pregnant later. Contraceptive use was reported by 79.6% of the patients and the most commonly used was oral contraceptive pills. Of those who had no contraception method, 60% admitted having unprotected sex. No statistically significant predictors of contraceptive use were identified. Conclusion: In this tertiary Lupus Clinic, most patients received effective contraceptive/family counselling and use contraceptive methods. Quality of the given information can still be improved.